The Influence of Organizational Culture, Work Motivation, and Job Satisfaction on Employee Performance at PT. Laksana Sejahtera - Iksan Maulana; Maswanto Maswanto (Universitas KH. Abdul Chalim Mojokerto, 2025)
The profitability of companies in the pharmaceutical and health research sectors listed on the Indonesia Stock Exchange (IDX) plays an important role in supporting economic growth and meeting public health needs. Various factors, such as the presence of female commissioners who bring different perspectives in strategic decision-making, the level of cash holding as an indicator of liquidity, and leverage as a reflection of the capital structure, are believed to affect the company's profitability. This study aims to analyze the influence of female commissioners, cash holding, and leverage on the profitability of pharmaceutical and health research sub-sector companies on the IDX in the 2019-2023 period, both individually and simultaneously. This study uses a quantitative method, the population in this study is companies included in the pharmaceutical and health research sub-sectors listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. A sample of the study was taken from all companies in the population that met certain criteria. The DKP variable had an insignificant negative influence on profitability with a significance value of 0.3694 (greater than 0.05). The CH variable also had an insignificant positive influence, with a significance value of 0.2101. Meanwhile, the DER variable showed a positive and significant influence on profitability with a significance value of 0.0133 (less than 0.05), which showed that the increase in DER had a real effect on increasing the company's profitability. The DKP and CH variables had an insignificant influence on profitability, as the significance value was greater than 0.05, although it showed a negative relationship for DKP and a positive relationship for CH. Meanwhile, the DER variable has a significant positive influence on profitability, because the significance value is less than 0.05, indicating that increasing DER can increase the company's profitability.